In vivo Antioxidant Activity of Dregea volubilis Linn. on Chromium (vi)-Induced Oxidative Stress in Albino Rats - Natarajan, Venkatesan; BA, Vishwanath (Free Radicals and Antioxidants)
Objectives: To evaluate the in vivo antioxidant potential of various extracts of Dregea volubilis on chromium (VI)-induced oxidative stress in albino rats. Methods: Animals were treated with plant extracts for 28 days and then oxidative stress was induced with a single doses of Chromium 30mg/kg (p.o.). Treated with 200 mg/kg (p.o.) of alcoholic extract of Dregea volubilis and determine the glutathione, SOD, catalase, peroxidise and transaminase enzymes levels. Results: The present studies revealed that Dregea volubilis has significant in vivo antioxidant activity and can be used to protect tissue from oxidative stress. The result showed that the activities of glutathione, SOD, catalase and peroxidise and tranaminase enzymes in group treated with chromium (VI) declined significantly than that of compared with control group. Conclusion: Ethanolic extract of Dregea volubilis in the dose of 200 mg/kg, p.o., has improved the glutathione, SOD, catalase, and peroxidase and transaminase enzymes levels significantly, which were comparable with Vitamin-E. Based on this study we conclude that Alcoholic extract of Dregea volubilis possesses in vivo antioxidant activity and can be employed in protecting tissue from oxidative stress.
Keywords: Dregea volubilis; In vivo Antioxidant activity; Chromium (VI); Vitamin-E; Free radicals; Oxidative stress